Unveiling Cognitive Dynamics and Classroom Culture: A Literature Review of Qualitative Research in Mathematics Education - Fadhlur Rohman; Lulu Sekardini; Nadila Nadila; Arvina Tri Septiani; Sri Hastuti Noer; Agung Putra Wijaya (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
This study aims to analyze the contribution of qualitative research approaches, particularly ethnography and case studies, in unveiling the interplay between classroom culture and students' mathematical thinking processes. Using a literature review method, this study synthesizes scholarly sources from 2015 to 2025 to deepen the understanding of how social context influences cognitive construction in mathematics education. The findings reveal that mathematical thinking is not an isolated cognitive activity but is deeply embedded in classroom culture. Ethnographic approaches effectively uncover the "hidden curriculum" and cultural norms that shape learning, while case studies provide granular insights into students' specific cognitive hurdles. The integration of these approaches with constructivist pedagogies, such as Realistic Mathematics Education (PMRI), offers a robust framework for creating more meaningful and culturally responsive learning environments. This study concludes that qualitative inquiry is essential for bridging the gap between individual cognition and social context, providing a humanistic perspective on mathematics education.